Implementation of Character Education for Elementary Students - Gunawan, Indra; Rusdarti, Rusdarti; Ahmadi, Farid (Journal of Primary Education, 2020)
Character education is essential to be carried out as early as possible in this millennial era in elementary schools. The characters that need to be developed are the values of discipline, love of the motherland, tolerance, religious, cooperation, independence, and fond of reading. This study aims to describe the implementation of character education in students through integration in the learning process and the culture of the school at Sekolah Dasar Negeri Pedurungan Tengah 02 Semarang City. The research is descriptive qualitative. Data were collected through interviews, observation, and study documentation, then analyzed through data reduction, and conclusion drawing. The technique of checking the validity of the data uses triangulation technique of interview, obervation, and documentation. The results of this study indicate that: (1) the implementation of character education in SD Negeri Pedurungan Tengah 02 is carried out through integration of character values in the learning process including the preparation of character lesson plans, the selection of learning methods, and the use of learning models (2) the implementation of character education for students in SD Negeri Pedurungan Tengah 02 is carried out through school culture which includes discipline, homeland love, tolerance, religious, independent, mutual cooperation, and reading hobit. It can be cocluded the character education in the school can be implemented properly in SD Negeri Pedurungan Tengah 02.